(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: To describe the clinical presentation, diagnostic imaging findings, and management of a rare case of bilateral temporomandibular joint (TMJ) ankylosis combined with dysplasia in a cat. Materials and Methods: A 4-month-old Bombay male cat, normally immunized and dewormed. Radiographic studies: Details of imaging techniques used to diagnose TMJ ankylosis and dysplasia: computed tomography (CT) scans were used to visualize the joint structures in greater detail using CT. Results: Out of the 21 blood biochemical abnormalities found in the laboratory test, creatinine, albumin, albumin/globulin, and total cholesterol all showed a significant decrease. The levels of phosphorus and α-amylase were marginally elevated. A three-dimensional CT scan revealed a malformed fusion of the right TMJ zygomatic arch and bilateral mandibular coronal process. Both TMJ dysplasia and ankylosis were discovered by the biochemical and physical 3-dimensional CT scans. Conclusion: The findings underscore the importance of a thorough clinical examination and imaging studies to assess the extent of the ankylosis and any associated dysplastic changes. This case emphasizes the need for increased awareness of TMJ disorders in felines and encourages further research into effective treatment protocols. J. Adv. Vet. Anim. Res., 12(2): 321–326, June 2025 http://doi.org/10.5455/javar.2025.l899